2015
DOI: 10.1136/annrheumdis-2015-eular.5781
|View full text |Cite
|
Sign up to set email alerts
|

SAT0621 Validation Study of Predictive Value of Capillaroscopic Skin Ulcer Risk Index (CSURI) in Scleroderma Patients Treated with Bosentan

Abstract: BackgroundCSURI is a capillaroscopic index, able to identify scleroderma (SSc) patients at high risk for new or non-healing digital ulcers (DU) in the next three months. CSURI has been validated, only in patients not treated with bosentan, in a large multicenter study in 2011.ObjectivesTo evaluate the predictive value of CSURI in SSc patients assuming bosentan for the prevention of DU.MethodsSeventy-six consecutive SSc patients treated with bosentan were enrolled in a multicenter study (F/M 4.4/1; mean age 56.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 2 publications
1
16
0
Order By: Relevance
“…Recent evidences, in large SSc cohorts, confirmed that the number of capillaries, as detected by NVC, is the most reliable capillaroscopic parameter for prediction of disease progression and detection of effects of therapies . Additionally, capillary density was used for the construction of several scoring systems such as the CSURI, the MES, and the simple day‐to‐day risk index . Other capillaroscopic parameters and derived quantitative indexes to evaluate disease activity in SSc through NVC imaging have been developed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidences, in large SSc cohorts, confirmed that the number of capillaries, as detected by NVC, is the most reliable capillaroscopic parameter for prediction of disease progression and detection of effects of therapies . Additionally, capillary density was used for the construction of several scoring systems such as the CSURI, the MES, and the simple day‐to‐day risk index . Other capillaroscopic parameters and derived quantitative indexes to evaluate disease activity in SSc through NVC imaging have been developed.…”
Section: Discussionmentioning
confidence: 99%
“…very good reliability of the software was confirmed, according to results of single measures ICC, in the difficult SSc image subsets, but also in the easier images obtained from healthy subjects and PRP subject subsets, used as controls.Recent evidences, in large SSc cohorts, confirmed that the number of capillaries, as detected by NVC, is the most reliable capillaroscopic parameter for prediction of disease progression and detection of effects of therapies 4,5,42,43. Additionally, capillary density was used for the construction of several scoring systems such as the CSURI, the MES, and the simple day-to-day risk index 4,28,44. Other…”
mentioning
confidence: 99%
“…This study has been validated in a dual center validation study and has been corroborated by the CAP study in which the performance of the scleroderma pattern had the same performance characteristics as counting the numbers of capillaries in one field of finger three of the dominant hand . The common and logical (as SSc is a disease with progressive obliteration of the microcirculation) denominator is that loss of capillaries (qualitatively described as “late” scleroderma pattern or quantitatively as “lowered” number of capillaries) is key criterion in prospective indici to predict new DU in an SSc population (Figure ) . In this way, for example, a patient with no critical digital ischemia at BL and also no DU at BL and a normal mean number of capillaries in the middle finger of the dominant hand is associated with a low risk to develop DU in the next six months.…”
Section: Association Between Capillaroscopy and Du In Sscmentioning
confidence: 64%
“…This index had a high positive and negative predictive predictivity in a patient population without vasomodifying therapy use (ERA s) at BL . Nevertheless, the good positive predictive values could not be reproduced in real‐life situations in which vasomodulating therapy use is being allowed . A second Belgian‐Italian pilot study investigated whether just counting the numbers of capillaries in eight fields of one linear mm was enough to be used as predictive formula.…”
Section: Association Between Capillaroscopy and Du In Sscmentioning
confidence: 99%
“…In a validation study, Sebastiani et al [ 9 ] demonstrated high predictive values for the development of DUs within 3 months, especially a high negative predictive value of 97%, but also a high positive predictive value of the CSURI of 81% in patients with a history of DUs. However, in another study by Sebastiani et al [ 17 ] a poorer performance of the CSURI with lower predictive values was also observed in a population of SSc patients treated with bosentan. Differences in DU prediction may therefore be explained by differences in vasoactive medications.…”
Section: Discussionmentioning
confidence: 90%